Peningkatkan Kemampuan Berhitung Permulaan Melalui Media Sempoa - Erna Olua; Diana Setyaningsih; Yohana B. Pabendan (JURNAL INOVATIF ILMU PENDIDIKAN, 2020)
The purpose of this study was to describe the increase in numeracy skills of 0-10 through the Abacus Media for Group B children in Integrated PAUD Nagallo Marannu, Puncak Jaya Regency, Academic Year 2017/2018. This research was conducted on group B children, amounting to 16 people. This research is an action research with the method of Kemmis and Taggart which consists of 4 stages, namely (plan, act, observe and reflect). This study consisted of 2 cycles, each of which consisted of 3 meetings. Data collection techniques using observation, field notes, and documentation. Data analysis using quantitative and qualitative. Quantitative data analysis was performed with statistical descriptions to compare pre-cycle to cycle II. Qualitative analysis is carried out by analyzing data from observations, field notes and verified documentation. The results showed that there was an increase in the ability to count numbers 0-10 through the abacus media with a score in the pre-cycle of 46.35% increasing to 66.66% in the first cycle and an increase of 82.29 in the second cycle with the very well developed category.Keywords: Ability to Count, Abacus Media, Early Childhood. DOI: http://dx.doi.org/10.23960/jiip.v2i1.21789